Brazilian Automatic License Plate Recognition: On the Importance to Add Vehicle Detection Phase in a Deep Learning Approach - Kamado, Lucas Mity; Silva, Murilo Varges da (Anais do Workshop de Visão Computacional (WVC), 2023)
In recent years, surveillance cameras have found wide-ranging applications, particularly in automatic vehicle license plate recognition to enhance security. One of the major problems of performing vehicle license plate recognition is the wide variety of existing license plate standards around the world, only in Brazil there are two standards, in addition, automatic license plate recognition depends directly on the quality of the input image. The objective of this paper is to evaluate whether adding the vehicle detection step improves license plate recognition rates in a deep learning approach. The method was implemented using the YOLOv8s model in all stages, however, two different approaches were proposed, one with and the other without the vehicle detection stage, the database used was the UFPR-ALPR, which only presents plates of the old Brazilian standard of 3 letters and 4 numbers.